Asking about wages: Results from the Bank of Canada's Wage Setting Survey of Canadian companies - David Amirault; Paul Fenton; Thérèse Laflèche (Bank of Canada, 2013)
The Bank of Canada conducted a Wage Setting Survey with a sample of 200 private sector firms from mid-October 2007 to May 2008. Results indicate that wage adjustments for the Canadian non-union private workforce are overwhelmingly time dependent, with a fixed duration of one year, and are clustered in the first four months of the year, suggesting that wage stickiness may not be constant over the year. Ad hoc adjustments between these fixed dates are rare, but when they do occur they are almost always upward and often in response to tight labour markets. The market wage rate is the most important factor managers consider when setting wages for their employees. Depending on firm size, different strategies are used to gain information about the market wage. Other important factors taken into account when setting wages include the firm's profitability, its difficulty in attracting staff and workers' productivity. While many managers acknowledge a link between the wage decision and inflation, very few use formal wage indexation rules such as a cost-of-living adjustment. Rather, most describe an informal backward-looking link. Survey results also suggest that managers are very reluctant to cut nominal base wages in times of weak demand. Managers are more likely to cut incentive pay, which would allow some flexibility in total compensation even if base pay is inflexible, or reduce the quantity of labour inputs (hours and employees).
Keywords: E24; J33; M52; 330; Labour markets; Transmission of monetary policy